2021
DOI: 10.4103/ijo.ijo_3550_20
|View full text |Cite
|
Sign up to set email alerts
|

Post-lockdown challenges for ophthalmologists during COVID-19 pandemic in India

Abstract: Purpose: The purpose of this study is to evaluate the post-lockdown challenges during Coronavirus disease 2019 (COVID-19) pandemic amongst the ophthalmologists in India. Methods: An online survey was sent to the practicing ophthalmologists across India. Data were collected from the responding ophthalmologists and analysed using Medcalc 16.4 software. Results: A total of 794 responses were obtained. Most respondents (51%) were in the age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Similarly, Arslan et al identified 47% of physicians reported their workload had also decreased (2021). Of the included studies, one reported only a reduction in workloads for ophthalmologists (Goel et al, 2021). The study reported a 90% reduction in workloads, specifically surgical work.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Arslan et al identified 47% of physicians reported their workload had also decreased (2021). Of the included studies, one reported only a reduction in workloads for ophthalmologists (Goel et al, 2021). The study reported a 90% reduction in workloads, specifically surgical work.…”
Section: Resultsmentioning
confidence: 99%
“…The current pandemic has had a heavy impact on the psychological, social, and economic impact on eye care professionals and hospitals. [ 19 20 ] In providing care for elective surgeries and clearing the backlog of surgeries that arouse due to lockdown, eye care facilities have been modified both structurally and functionally to provide safe service. [ 4 17 18 21 22 23 24 25 26 27 ] Apart from several general modifications in the clinical and surgical setting, a few major impactful modifications have been the use of teleconsultation services and immediate sequential bilateral cataract surgery that minimizes post-operative visits.…”
Section: Discussionmentioning
confidence: 99%
“…It has adversely affected the clinical and surgical training of residents, continued medical training of doctors, financial loss to those in private practice, and a physically as well as mentally hostile work condition for those working in COVID-19 hospitals in the government setup. [ 9 11 12 13 14 ] In the current study, we assessed the ophthalmic practice pattern among ophthalmologists in India during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Ophthalmology practice was one of the worst-hit medical fields, as a majority of cases require treatment for elective conditions. [ 5 9 ] This was detrimental for both the ophthalmologists as well as the patients suffering from various ophthalmic conditions. Various ophthalmologists suffered major financial loss during this era due to the altered clinical practice.…”
mentioning
confidence: 99%